ANALISIS KERJASAMA GURU BIMBINGAN KONSELING (BK) DENGAN GURU BIDANG STUDI DALAM MENGATASI KESULITAN BELAJAR PADA SISWA DI SMP KOTA BANDA ACEH - Muspida Rahmawati; M. Husen; Nurbaity Bustamam (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2018)
Problem that often occur in teaching learning processes is the trable of learning. Trouble of learning not only in academic. But, also in non-academic, therefore need to handling cooperation between guidance counseling teacher and the study teacher, so the aim of the stdy to know cooperation between guidance counseling teacher and the study teacher in addressing the trouble of learning on student in SMP Negeri Kota Banda Aceh. The approach research methodologhy conduched in this research are qualitative approach with descriptive method accompanying the tecniques of data collection the writer use interview and documentation. Techniques of processing and analysis the data were applyed descriptive qualitative analysys. The result of this research showed that cooperation of guidace counseling teacher with the study teacher to superintend the trobles of learning is quite interwined, but not overall, cooperation that occur in the session of data collection, both sides exchanged give the data about the state of student, both the data is writen and the data is verbal about the student, data presentation, the valve of raport, the valve of UTS (the middle test of semester), behavior attandance, although visit their house according the situation and conditions, cooperation between guidance counseling with the study teacher that unable to overcome by guidance counseling teacher and the study teacher. So, it need to involve the other party as trustee of the class, although the parent of student aceording tothe research above we can take the conclution that cooperation between guidance counseling teacher with the study teacher to addressing the trouble of learning not always interwined, but it is hanging with the problem of students when the session of data collecition.